2017
DOI: 10.1007/s00125-017-4367-3
|View full text |Cite
|
Sign up to set email alerts
|

The association of depressive symptoms and diabetes distress with glycaemic control and diabetes complications over 2 years in newly diagnosed type 2 diabetes: a prospective cohort study

Abstract: Aims/hypothesis We examined the associations between depressive symptoms and diabetes distress with glycaemic control and diabetes complications over 2 years, after diagnosis of type 2 diabetes. Methods In a multi-ethnic, primary care cohort (n = 1735) of adults, all with recent (<6 months) diagnosis of type 2 diabetes, we measured the associations between depressive symptoms (Patient Health Questionnaire-9 [PHQ-9] score ≥10) and diabetes distress (Problem Areas in Diabetes [PAID] score ≥40), with change in 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 43 publications
4
62
0
7
Order By: Relevance
“…ORs instead of HRs; for full details, see Table ). In terms of macrovascular complications, the results of two studies supported the findings of the meta‐analysis . Another study found a significantly increased risk only for angina (HR = 1.40; 95% CI: 1.06–1.84), but not for the objective, coronary artery disease (no statistics were provided for the latter).…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…ORs instead of HRs; for full details, see Table ). In terms of macrovascular complications, the results of two studies supported the findings of the meta‐analysis . Another study found a significantly increased risk only for angina (HR = 1.40; 95% CI: 1.06–1.84), but not for the objective, coronary artery disease (no statistics were provided for the latter).…”
Section: Resultssupporting
confidence: 56%
“…Three of the 22 studies examined people with Type 1 diabetes, [23,29,30] nine examined people with Type 2 diabetes, [16][17][18][19][31][32][33][34][35] and 6 examined people with either Type 1 or Type 2 diabetes [36][37][38][39][40][41]. Four studies did not specify the type of diabetes [42][43][44][45].…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these studies were limited by their cross-sectional design. One recently published study found that diabetes distress (defined by a PAID score of ≥40) was not associated with worsening HbA 1c levels in individuals with type 2 diabetes [21]. This study was limited by a very short follow-up duration of only 2 years, and further evidence is needed to evaluate an association between diabetes distress and glycaemic control.…”
Section: Discussionmentioning
confidence: 88%
“…One found that general (not diabetes-specific) distress, as measured by the Mental Health Inventory 5, was associated with a 1.8-fold higher risk of mortality and a 1.7-fold higher risk of having a cardiovascular event in 1533 Swedish individuals with type 2 diabetes during a mean follow-up of 5.4 years [22]. The other prospective study evaluated the association between diabetes-specific distress, measured using PAID, and the subsequent risk of diabetic complications among individuals in the UK, and found that a PAID score of ≥40 was not associated with microvascular and macrovascular complications in individuals with type 2 diabetes during the 2-year follow-up [21]. However, we believe that 2 years is too short a period to evaluate the effect of complications, and further studies are needed to examine the prospective association between diabetes distress and diabetes complications.…”
Section: Discussionmentioning
confidence: 99%